Analysis of The Effect of Three-Month DCA Accuracy on Optimistic Bias In Fulfilling Cooking Oil For DCA Recipient Families - Paramitha, Tarissya (Pelopor Publikasi Akademika, 2024)
Cooking oil is one of the basic needs for the people of Indonesia and is included in the nine staples. Currently, there is an increase in the price of cooking oil as a result of the price of crude palm oil on the international market increasing and reaching the highest price ever recorded in history. So that the government’s action to overcome the increase in cooking oil prices is to provide Direct Cash Assistance in the form of electronic money or non-cash assistance with the main target being Families Receiving Non-Cash Food Assistance and Family Hope Program and Street Vendors who sell fried food. This study aims to see the bias that occurs against DCA given to beneficiary families and provide suggestions for the government based on the results of cost accuracy in fulfilling cooking oil for 3 months. The method used in this research is the statistical test of single sample mean and double sample mean to determine the accuracy of respondents’ answers to the movement of cooking oil prices. The results showed that there was an optimistic bias towards the estimation of cooking oil prices by the community. People expect the price of cooking oil to fall, but in actual conditions the price of cooking oil for a month from May to June shows a fixed price neither rising nor falling.